It Tastes like the East…: The Problem of Taste in the GDR (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | This essay uses the topic of taste, specifically taste for food, as a way of unpacking the history of the GDR and East-West relations during the late Cold War. It explores the question of East German tastes from two angles: West German fantasies about the inadequacies of the GDR’s food system, and East German nutritionists’ unsuccessful struggles to regulate popular tastes. In particular, it focuses on the moment when popular taste was seen as a serious problem by the GDR state—during the rise of the obesity epidemic in the 1970s and 1980s. Résumé | Cet essai utilise le thème du goût, spécifiquement le goût pour la nourriture, comme un moyen de dévoiler l’histoire de la RDA et les relations Est-Ouest pendant la fin de la guerre froide. Il examine la question des goûts de l’Allemagne de l’Est sous deux angles: Les fantaisies des ouest-allemands sur les insuffisances du système alimentaire de la RDA, et les luttes infructueuses des spécialistes de la nutrition est-allemands pour réglementer les goûts populaires. L’essai se concentre en particulière sur le moment où le goût populaire a été considéré comme un problème grave par l’état de la RDA—pendant l’augmentation de l’épidémie d’obésité dans les années 1970 et 1980.